1185. Impact of Bloodstream Infections Caused by Multidrug-resistant Organisms on Performance Status: A KARS-Net Study. (26th November 2018) - Huh, Kyungmin; Chung, Doo Ryeon; Ko, Jae-Hoon; Ha, Young Eun; Kim, Si-Ho; Oh, Suhyun; Jang, Sukbin; Mun, Seokjun; Huh, Hee Jae; Lee, Nam Yong; Cho, Sun Young; Kang, Cheol-In; et al.
Abstract: Background: Infections caused by multidrug-resistant (MDR) organisms are associated with poorer clinical outcomes and higher economic burden. However, there has been limited data on the impact of MDR infection on the performance status of patients. Methods: Patients with bloodstream infections by S. aureus, E. faecium, E. coli, K. pneumoniae, P. aeruginosa, and A. baumannii have been identified prospectively as a part of a multicenter nationwide surveillance for antimicrobial resistance. Medical records of the patients enrolled from July 2015 through December 2016 were reviewed for demographic, clinical, microbiologic characteristics, and patient outcome. MDR was defined as MRSA, VRE, and nonsusceptibility to one or more agents in three or more different classes of antibiotics for Gram-negative bacteria. Performance status was evaluated by Eastern Cooperative Oncology Group (ECOG) Performance Status before admission and at discharge. Primary outcome was any decline in ECOG at discharge. Multiple logistic regression was used to identify independent risk factors for ECOG decline. Results: A total of 19 hospitals participated to the network. The numbers of subjects were 410 for S. aureus, 392 for E. faecium, 708 for E. coli and K. pneumoniae, and 678 for P. aeruginosa and A. baumannii . In univariate analysis, bacteremia by MDR organisms was associated with ECOG decline only in patients with P. aeruginosa (18.4% vs. 10.3%, OR 1.962, 95% CI 1.132–3.399) and A. baumannii (27.6% vs. 11.8%, OR 2.834, 95% CI 1.328–6.045) infections. Patients with MDR K. pneumoniae infection had lower risk of ECOG decline (6.6% vs. 15.8%, OR 0.378, 95% CI 0.183–0.780). Multivariable analysis also showed that infection by MDR organism was independently associated with ECOG decline in patients with P. aeruginosa or A. baumannii infections (OR 2.068, 95% CI 1.478–2.895), but not with other MDR organisms. Comorbidities and initial ECOG showed higher effect size in patients with S. aureus and E. faecium infections. Conclusion: In this large multicenter nationwide study, bloodstream infections caused by MDR P. aeruginosa and A. baumannii were associated with higher risk of decline in performance status at discharge. MDR status did not show association in infections by other species. Disclosures: All authors: No reported disclosures.